The Institutional Building of Science and Innovation Diplomacy in Latin America: Toward a Comprehensive Analytical Typology - da Silva, Renan Gonçalves Leonel; Ferreira, Gabriela Gomes Coelho; Onuki, Janina; Oliveira, Amâncio Jorge Nunes de (Frontiers in Research Metrics and Analytics, 2021)
Science and Innovation Diplomacy (S&ID) has emerged in recent years as a relevant scholarly movement and interdisciplinary research agenda internationally. This field is promoting a significant impact on the understanding of the cultural and political dynamics of Science, Technology and Innovation (ST&I), implementing initiatives from local to global level. Notwithstanding, S&ID is growing asymmetrically around the world, setting up over a particular configuration in the so-called Global South (GS) societies. In Latin America (LA), although S&ID is a recent, unequal and intra-nationally fragmented process, there are important achievements that have been able to create a favorable mix of approaches, agendas, and practices in this field. Addressing the scope of the special issue “Science Diplomacy and Sustainable Development: Perspectives from Latin America,” this article aims to present a comprehensive analytical typology to the study of the emerging experiences of S&ID in LA, catching the diversity of this research agenda. This is a qualitative merged method-based study, sustained by a literature review, documentary research, online data analysis, and typology building. We understand S&ID in LA as a tentative re-organization of different states and subnational actors around the study and institutionalization of the governance of contemporary transformations on the systems of ST&I.